Innovative Language Teaching and Learning at University: Integrating Informal Learning into Formal Language Education - Min Huang (Brock University, 2020)
The edited book Innovative Language Teaching and Learning at University: Integrating Informal Learning into Formal Language Education, built on the 2017 Innovative Language Teaching and Learning at University conference (InnoConf), collected chapters with the theme: "Integrating informal learning into formal language education" (p. 3). Focusing on the exploration of innovative technologies for the purpose of language learning, the editors present a variety of approaches, including online courses, Wikipedia, social networking apps, online learning platforms, game-based tasks, video-based support, and Twitter. Based on the aims of the articles, the editors organized the chapters into two sections, with the first section addressing users' feelings about these technologies and the second section addressing users' evaluations of the technologies. The third section is an interview between the editor Tita Beaven and Richard Simcott, a founder of the Polyglot Conference. The interview emphasizes the importance of learning languages in informal ways.